Land use and climate change interactions in Central Vietnam : LUCCi - Nauditt, Alexandra; Ribbe, Lars (Water resources development and management., 2017)
This book summarizes the key findings of a five-year interdisciplinary research project funded by the German Federal Ministry of Research and Education (BMBF). It serves as a typical case study for a rapidly growing and developing urban center -- Da Nang City, which is surrounded by remote areas characterized by increasing migration and limited development. A number of German and Vietnamese universities and international institutions participated in the project, contributing their particular expertise to assess the data-scarce region under study, two provinces in central Vietnam with a combined area of ca. 12,000 km².